Um modelo de calibração de segunda ordem para determinação espectrofluorimétrica de hidrocarbonetos policíclicos aromáticos em bebidas destiladas - Silva, Amanda Cecília da Silva (2015)
Alcoholic beverage consumption increases annually worldwide and consequently the higher is the intake of harmful compounds that is present in these products, such as polycyclic aromatic hydrocarbons (PAH's) which has attracted the attention of researchers because of their carcinogenic capacity. The spirits is the class of drinks most affected by the presence of this group of contaminants (HPA's) that reaches it by burning the raw material used in the production. Despite the existing concern about the HPA's there is still no legislation or control for these contaminants in spirits, so as soon as possible the creation of legislation is necessary and for this, is necessary to develop rapid, robust and low waste production analytical methods. Most quantitation methods for PAH's in food uses HPLC-FLU or GC-MS, but the use of liquid or gas chromatography coupled to mass spectra generates huge amount of waste beyond the analysis time and high associated costs. In this work we present a rapid methodology, relatively simple and low cost to simultaneous quantification of five HPA's (BaP, FL, AC, AN and P) in three types of spirits (rum, cachaça and vodka) using fluorescence spectroscopy EEM 3D and second order calibration to circumvent the problems caused by the complexity of the matrix by the second order advantage. Calibration models were built by PARAFAC and U-PLS/RBL using pure analyte individual standard solutions. And the models were validated using a set of analytes mixtures adding an interfering (FE). For the development of validation blends the Taguchi design was used. The validation parameters obtained were satisfactory for both models (PARAFAC and U-PLS / RBL), with REP on a range from 4.58% to 8.55% and 1.75% to 9.16% respectively. The application of calibration models in real samples is still being processed. processed. The application of calibration models in spirits showed good performance with recovery values in the range of 85.99% to 115.18% for PARAFAC and 81.02% to 106.05% for U-PLS / RBL. Therefore, we can say that the models built had satisfactory performance for the determination of PAH's in spirits, reaching the second advantage, with little generation of waste, simplicity and low cost associated.